Enhancement of photodynamic inactivation of Staphylococcus aureus biofilms by disruptive strategies - Gándara, Lautaro (2017)
Photodynamic inactivation (PDI) has been used to inactivate microorganisms through the use of photosensitizers and visible light. On the one hand, near-infrared treatment (NIRT) has also bactericidal and dispersal effects on biofilms. In addition, dispersal biological tools such as enzymes have also been employed in antibiotic combination treatments. The aim of this work was to use alternative approaches to increase the PDI efficacy, employing combination therapies aimed at the partial disruption of the biofilms, thus potentially increasing photosensitizer or oxygen penetration and interaction with bacteria. To that end, we applied toluidine blue (TB)-PDI treatment to Staphylococcus aureus biofilms previously treated with NIRT or enzymes and investigated the outcome of the combined therapies. TB employed at 0.5 mM induced per se 2-log drop in S. aureus RN6390 biofilm viability. Each NIRT (980-nm laser) and PDI (635-nm laser) treatment induced a further reduction of 1-log of viable counts. The combination of successive 980- and 635-nm laser treatments on TB-treated biofilms induced additive effects, leading to a 4.5-log viable count decrease. Proteinase K treatment applied to S. aureus of the Newman strain induced an additive effect on PDI mortality, leading to an overall 4-log decrease in S. aureus viability. Confocal scanning laser microscopy after biofilm staining with a fluorescent viability test and scanning electron microscopy observations were correlated with colony counts. The NIRT dose employed (227 J/cm2) led to an increase from 21 to 47 °C in the buffer temperature of the biofilm system, and this NIRT dose also induced 100% keratinocyte death. Further work is needed to establish conditions under which biofilm dispersal occurs at lower NIRT doses.